2015
DOI: 10.1021/acssuschemeng.5b00023
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Kinetic Modeling Studies on the Sulfuric Acid Catalyzed Conversion of d-Fructose to 5-Hydroxymethylfurfural and Levulinic Acid in Water

Abstract: Levulinic acid (LA) and 5-hydroxymethylfurfural (HMF) have been identified as promising biomass-derived platform chemicals. A kinetic study on the conversion of D-fructose to HMF and LA in water using sulfuric acid as the catalyst has been performed in batch setups. The experiments were carried out in a temperature window of 140−180 °C, using sulfuric acid as the catalyst (0.005−1 M) and an initial D-fructose concentration between 0.1 and 1 M. A kinetic model for the conversion of D-fructose to HMF and the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(178 citation statements)
references
References 34 publications
(71 reference statements)
12
161
0
Order By: Relevance
“…However, it is not possible to determine the temperature at which the LA yield is at its maximum, as not all of the HMF has been reacted to LA within the batch time of 2 h. The effect of the inulin intake on the yield of LA and HMF is shown in Figure 8 at a constant temperature of 180 °C and a catalyst concentration of 0.01 M. The HMF yield is a function of the intake, with higher intakes leading to lower HMF yields. These findings are in line with a kinetic study from our group on the reaction of D-fructose to HMF and LA using a Brönsted acid (sulphuric acid) [55]. This observation was rationalised by considering that the order of substrates for the reactions leading to humins is higher than those for the desired main reactions.…”
Section: Effect Of Process Conditions On Hmf and La Yields For Inulinsupporting
confidence: 86%
See 1 more Smart Citation
“…However, it is not possible to determine the temperature at which the LA yield is at its maximum, as not all of the HMF has been reacted to LA within the batch time of 2 h. The effect of the inulin intake on the yield of LA and HMF is shown in Figure 8 at a constant temperature of 180 °C and a catalyst concentration of 0.01 M. The HMF yield is a function of the intake, with higher intakes leading to lower HMF yields. These findings are in line with a kinetic study from our group on the reaction of D-fructose to HMF and LA using a Brönsted acid (sulphuric acid) [55]. This observation was rationalised by considering that the order of substrates for the reactions leading to humins is higher than those for the desired main reactions.…”
Section: Effect Of Process Conditions On Hmf and La Yields For Inulinsupporting
confidence: 86%
“…This suggests that the order in catalyst concentration is not equal for all reactions in the network. A similar trend was observed for a detailed kinetic study by our group on the conversion of D-fructose to HMF/LA using sulphuric acid as the catalyst [55]. It is not possible to assess the effect of the catalyst concentration on the LA yield, as the HMF conversion is not yet quantitative for the longest batch time (2 h).…”
Section: Effect Of Process Conditions On Hmf and La Yields For Inulinsupporting
confidence: 72%
“…For fructose alone, the highest reported HMF yield in water using sulfuric acid is 53 mol % (initial fructose concentration of 0.1 M, a sulfuric acid concentration of 0.01 M and a temperature of 180 °C). 40 For glucose, the HMF yield is considerably lower and for instance Girisuta et al reported a maximum yield of 5 mol % in water using sulfuric acid as the catalyst in a similar window of process conditions. 8 As such, the value of 22 mol % for sucrose is in line with the literature, particularly when considering that the initial inversion of sucrose to fructose and glucose is fast and essentially quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…The group led by Heeres, for example, used modified Arrhenius equations with (1) power law dependence of acid catalyst concentration, and (2) power law dependence of reaction order. They investigated the kinetics of the acid-catalyzed conversion of fructose to HMF [23], HMF to levulinic acid [24], and glucose to levulinic acid [25]. However, kinetic parameters which are determined experimentally depend to a great extent on the setup and the procedure of the experiments themselves [26].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the study, the mass percentage of acid [27,28], hydronium concentration at ambient conditions [20], hydronium concentration at reaction conditions [23,25], an activity term [29], or multiple factors [30] may be used in modified Arrhenius equations.…”
mentioning
confidence: 99%